A paixão de conhecer o mundo - Nascimento, Hostina Maria F. do; Silva, Maria das Graças Silvestre da; Silva, Rosemary Giol da (Revista Educação em Questão, 1989)
FREIRE, Madalena. A paixão de conhecer o mundo. Rio de Janeiro, Ed. Paz e Terra, 1983.